Metabolic fate of fructose ingested with and without glucose in a mixed meal. - Theytaz, F; de Giorgi, S; Hodson, L; Stefanoni, N; Rey, V; Schneiter, P; Giusti, V; Tappy, L (MDPI AG, 2014)
Ingestion of pure fructose stimulates de novo lipogenesis and gluconeogenesis. This may however not be relevant to typical nutritional situations, where fructose is invariably ingested with glucose. We therefore assessed the metabolic fate of fructose incorporated in a mixed meal without or with glucose in eight healthy volunteers. Each participant was studied over six hours after the ingestion of liquid meals containing either 13C-labelled fructose, unlabeled glucose, lipids and protein (Fr + G) or 13C-labelled fructose, lipids and protein, but without glucose (Fr), or protein and lipids alone (ProLip). After Fr + G, plasma 13C-glucose production accounted for 19.0% ± 1.5% and 13CO2 production for 32.2% ± 1.3% of 13C-fructose carbons. After Fr, 13C-glucose production (26.5% ± 1.4%) and 13CO2 production (36.6% ± 1.9%) were higher (p < 0.05) than with Fr + G. 13C-lactate concentration and very low density lipoprotein VLDL 13C-palmitate concentrations increased to the same extent with Fr + G and Fr, while chylomicron 13C-palmitate tended to increase more with Fr + G. These data indicate that gluconeogenesis, lactic acid production and both intestinal and hepatic de novo lipogenesis contributed to the disposal of fructose carbons ingested together with a mixed meal. Co-ingestion of glucose decreased fructose oxidation and gluconeogenesis and tended to increase 13C-pamitate concentration in gut-derived chylomicrons, but not in hepatic-borne VLDL-triacylglycerol (TG). This trial was approved by clinicaltrial. gov. Identifier is NCT01792089.